Constraining the geometry of the dipping atoll 4U 1624–49 with X-ray spectroscopy and polarimetry - Gnarini, Andrea; Saade, M. Lynne; Ursini, Francesco; Bianchi, Stefano; Capitanio, Fiamma; Kaaret, Philip; Matt, Giorgio; Poutanen, Juri; Zhang, Wenda (EDP Sciences, 2026)
We present the spectro-polarimetric results obtained from simultaneous X-ray observations with IXPE, NuSTAR, and NICER of the dipping neutron star X-ray binary 4U 1624-49. This source is the most polarized Atoll source so far observed with IXPE, with a polarization degree of 2.7%+/- 0.9% in the 2-8 keV band during the nondip phase and marginal evidence of an increasing trend with energy. The higher polarization degree compared to other Atolls can be explained by the high inclination of the system (i approximate to 60 degrees). The spectra are well described by the combination of soft thermal emission, a Comptonized component, and reflection of soft photons off the accretion disk. During the dips, the hydrogen column density of the highly ionized absorber increases while the ionization state decreases. The Comptonized radiation seems to be the dominant contribution to the polarized signal, with additional reflected photons that contribute significantly even though their fraction in the total flux is not high.